Optimal Sixteenth Order Convergent Method Based on Quasi-Hermite Interpolation for Computing Roots - Fiza Zafar; Nawab Hussain; Zirwah Fatimah; Athar Kharal (The Scientific World Journal)
We have given a four-step, multipoint iterative method without memory for solving nonlinear equations. The method is constructed by using quasi-Hermite interpolation and has order of convergence sixteen. As this method requires four function evaluations and one derivative evaluation at each step, it is optimal in the sense of the Kung and Traub conjecture. The comparisons are given with some other newly developed sixteenth-order methods. Interval Newton’s method is also used for finding the enough accurate initial approximations. Some figures show the enclosure of finitely many zeroes of nonlinear equations in an interval. Basins of attractions show the effectiveness of the method.